Determination of polyphenolic content, HPLC analyses and DNA cleavage activity of Malaysian Averrhoa carambola L. fruit extracts - Khanam, Z.; Sam, K.H.; Zakaria, N.H.B.M.; Ching, C.H.; Bhat, I.U.H. (Journal of King Saud University, 2015)
In developing countries, the increasing gap between population growth and food supply has created renewed interest in finding reliable and cheap natural resources of nutraceutical value and health promoting properties. Therefore, the present study deals with the phytochemical analyses and DNA cleavage activity of Averrhoa carambola L. fruit (starfruit) extracts. The phytochemical studies involve colour tests and quantification of phenolics and flavonoids of the prepared ethanolic and aqueous extracts. Identification of phenolic acids and flavonoids present in the extracts were conducted by high performance liquid chromatography (HPLC) equipped with diode array detector (DAD). DNA cleavage activity of the extracts was evaluated through gel electrophoresis against plasmid Escherichia coli DNA at different concentrations (0.125–0.60 μg/μl). The results of the study exhibited that the starfruit is a rich source of polyphenols and all the extracts exhibited a dose dependent DNA cleavage activity, whereas ethanolic extract induced more cleavage as compared to the aqueous extract. In conclusion, the present study provides preliminary evidence with regard to nutraceutical value of the fruit. So, further extensive study is a prerequisite to exploit DNA cleaving properties of the fruit extracts for therapeutic application.Khanam,